Ревматоїдний артрит – сучасний стан проблеми - Ногас, Анжела; Nogas, Andzhela (Східноєвропейський національний університет імені Лесі Українки, 2013)
За даними аналізу літературних джерел висвітлено основні ланки патогенезу ревматоїдного артриту, показано, що гормональний фон має важливе значення в його перебігу. Описано основні клінічні симптоми, ступені активності ревматоїдного процесу та критерії визначення функціональної здатності хворого. Відзначено, що лікування хворих на ревматоїдний артрит вимагає міждисциплінарного підходу. У статті узагальнено й представлено сучасні погляди та тенденції щодо проведення фізичної реабілітації хворих на ревматоїдний артрит. Розглянуто основні підходи до призначення засобів лікувальної фізичної культури в системі фізичної реабілітації хворих на ревматоїдний артрит на стаціонарному етапі лікування. Ґрунтовно описано застосування фізичних вправ при ревматоїдному артриті таких видів: статичних, пасивних, активних із допомогою, активних з опором. According to the analysis of literary resources we have highlighted the main sections of pathogenesis of rheumatoid arthritis. It was shown that hormone background has an important meaning in its flow. We have described main clinic sympthoms, stages of activity of rheumatoid process and criteria of defining of functional abilities of an ill person. Treatment of an ill person with rheumatoid arthritis needs interdisciplinary approach. In the article we have generalized and presented modern views and tendencies concerning conducting of physical rehabilitation of the ill with rheumatoid arthritis. We have also studied approaches to prescription of means of exercise therapy in the system of physical rehabilitation of the ill with rheumatoid arthritis on stationary stage of treatment. We have also described applying of physical exercises in case of rheumatoid arthritis of the following types: statistical, passive, active with support, active with resistance.
Rheumatoid Arthritis – Modern Condition of the Problem
Keywords: ревматоїдний артрит; фізична реабілітація; лікувальна фізична культура; фізичні вправи; rheumatoid arthritis; physical rehabilitation; exercise therapy; physical exercises